Loop-Mediated Isothermal Amplification (LAMP) assay for rapid detection of Banana Bunchy Top Virus (BBTV) infecting Abaca (Musa textilis Nee) in the major abaca plantations in Caraga Region (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
This study evaluated the diagnostic efficacy of two methods for detecting Banana Bunchy Top Virus (BBTV) in abaca: conventional Polymerase Chain Reaction (PCR) and a novel colorimetric Loop-Mediated Isothermal Amplification (LAMP) assay. The study's purpose was to determine which method is more effective for field-based surveillance in the Philippines, a country with significant economic reliance on abaca production. A total of 243 leaf samples from key abaca-producing municipalities in the Caraga Region were collected and tested.The LAMP assay exhibited a significantly higher detection rate, identifying 85.2% of samples as positive compared to only 35.8% by conventional PCR (χ2 = 121.92, df = 1, p < 0.001). This diagnostic superiority was consistent across all four provinces surveyed, with the most pronounced difference in Surigao del Norte, where LAMP detected 86.04% of infections compared to a mere 2.33% by PCR. These findings reveal a substantial, previously hidden, reservoir of asymptomatic and low-titer BBTV infections that evade detection by traditional methods.The novelty of this study lies in its demonstration that LAMP is not only more sensitive but also uniquely suited for resource-limited settings due to its simple visual readout and lack of reliance on complex laboratory equipment. The results highlight that relying solely on symptom-based surveillance severely underestimates the true disease prevalence. The study concludes that adopting LAMP as a cornerstone of national surveillance efforts could provide a critical advantage in curbing the silent spread of BBTV, ensuring the sustainability of the abaca industry in the Philippines.
Keywords: Abaca; Banana Bunchy Top Virus (BBTV); LAMP; Diagnostics; Surveillance